Observations of Gaia Microlensing Events in Abastumani - Kvernadze, T.; Kvaratskhelia, O.; Kozlov, V.
Gaia is now one of the most successful and leading transient space mission. It discovers nearly 2000 objects annually from all over the sky, down to about 20 mag, covering all possible classes of transients from supernovae and cataclismic variables to rare phenomena like microlensing events or pair-instability supernovae. The long time baseline of Gaia data allows for more robust detections of photometric anomalies. The gravitational microlensing method is especially sensitive to compact-object lenses in the Milky Way, including white dwarfs, neutron stars or black holes. The team, involved in the photometric follow-up observations of Gaia microlensing events, is collaborating with the International Working Group of Gaia Science Alerts through the BHTOM platform since 2020. Currently, we mainly use the 36-cm SCT-14 telescope of the Georgian National Astrophysical Observatory (Abastumani, Georgia) which is equipped with large format CCD and UBVRI filter set. At present we have processed and submitted for combined light curves observational data of 16 moderately bright Gaia alerts. Some of them clearly show the microlensing event type of light curves, though they need more detailed investigation. Here we present preliminary results of data connected with two such events: Gaia19dke and Gaia21dnc.
Keywords: Astronomy